Cavitation control on a 2D hydrofoil through a continuous tangential injection of liquid: Experimental study - Timoshevsky M. V.; Zapryagaev I. I.; Pervunin K. S.; Markovich D. M. Dmitry Markovich (2016, 2016)
Title screen